2015
DOI: 10.1158/1541-7786.mcr-14-0412
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant LPL Expression, Driven by STAT3, Mediates Free Fatty Acid Metabolism in CLL Cells

Abstract: While reviewing chronic lymphocytic leukemia (CLL) bone marrow slides we identified cytoplasmic lipid vacuoles in CLL cells but not in normal B cells. Because lipoprotein lipase (LPL), which catalyzes hydrolysis of triglycerides into free fatty acids (FFAs), is aberrantly expressed in CLL, we investigated whether LPL regulates the oxidative metabolic capacity of CLL cells. We found that unlike normal B cells, CLL cells metabolize FFAs. Because STAT3 is constitutively activated in CLL cells and because we ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 43 publications
7
87
0
Order By: Relevance
“…In CLL, STAT3 is constitutively phosphorylated on serine 727 residue [70,71] and activates genes that provide CLL cells with survival advantage [7174]. Indeed, we have recently found that in CLL phosphoserine STAT3 binds to and activates the promoter of lipoprotein lipase (LPL) [75]. …”
Section: Altered Lipid Metabolism In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…In CLL, STAT3 is constitutively phosphorylated on serine 727 residue [70,71] and activates genes that provide CLL cells with survival advantage [7174]. Indeed, we have recently found that in CLL phosphoserine STAT3 binds to and activates the promoter of lipoprotein lipase (LPL) [75]. …”
Section: Altered Lipid Metabolism In Cllmentioning
confidence: 99%
“…Unlike normal B lymphocytes CLL cells store lipids in cytoplasmic vacuoles and utilize FFAs to produce energy via oxidative phosphorylation [75]. Metabolomic analysis of CLL cells identified increased levels of FFAs and triglyceride degradation products, suggesting that these changes are induced by downregulation of microRNA (miR)-125 and a reciprocal increase in lipolysis-facilitating enzymes [79].…”
Section: Altered Lipid Metabolism In Cllmentioning
confidence: 99%
“…To profile the expression of the NF-κB target genes, we used an RT 2 Profiler PCR Array kit (Qiagen Sciences, Germantown, MD) This 96-well assay profiles the expression of 83 NF-κB target genes and has wells for 3 different housekeeping genes, a genomic DNA contamination control, 3 replicate reverse transcription controls, and 3 replicates of positive polymerase chain reaction (PCR). Real-time PCR was performed according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Serine pSTAT3 has biologic activities similar to those of tyrosine pSTAT3: Serine pSTAT3 is shuttled to the nucleus, binds to DNA, activates genes known to be activated by tyrosine pSTAT3, and provides CLL cells with a survival advantage (5, 912) and proliferation capacity (12, 13). …”
Section: Introductionmentioning
confidence: 99%